Uji Efektivitas Nefroprotektive Ekstrak Buah Kopi (Coffea arabica L.) Terhadap Gambaran Histopatologi dan Penanda Inflamsi Pada Tikus Yang Diinduksi Gentamisin - Anas Tasya Glori Br Ginting; Asyrun Alkhairi Lubis; Refi Ikhtiari (Journal of Pharmaceutical and Sciences, 2026)
Gentamicin is an aminoglycoside antibiotic widely used in the treatment of severe bacterial infections; however, its clinical application is limited due to nephrotoxic effects. Gentamicin-induced nephrotoxicity is closely associated with oxidative stress and inflammatory responses, which contribute to tubular damage and renal dysfunction. Coffee fruit (Coffea arabica L.) contains various bioactive compounds, including phenolics, flavonoids, and polyphenols, which exhibit antioxidant and anti-inflammatory activities and may provide renal protection. This study aimed to evaluate the nephroprotective effectiveness of coffee fruit extract against gentamicin-induced kidney injury in rats based on histopathological features and inflammatory markers. This experimental in vivo study used male Wistar rats divided into five groups: normal control, gentamicin control, and gentamicin combined with coffee fruit extract at doses of 100, 200, and 400 mg/kg body weight. Gentamicin was administered intraperitoneally to induce nephrotoxicity, while the extract was given orally for 14 days. Serum interleukin-6 (IL-6) levels were measured using enzyme-linked immunosorbent assay, and kidney tissues were examined histopathologically using hematoxylin–eosin staining. The results showed that gentamicin significantly increased serum IL-6 levels and caused moderate renal histopathological damage. Administration of coffee fruit extract significantly reduced IL-6 levels at doses of 200 and 400 mg/kg body weight (p<0.05) and improved renal histopathological features in a dose-dependent manner, with the highest dose showing the most pronounced protective effect. In conclusion, coffee fruit extract demonstrates nephroprotective potential against gentamicin-induced renal injury by reducing inflammatory responses and improving kidney histopathology.